Formulating Policies to Control Cigarette Consumption in Various Countries: A Literature Review - Ratnasari, Leni; Supriyanto, (Research in Management of Technology and Business, 2024)
The purpose of this study is to understand the implementation of the analysis of the elasticity of cigarette price demand in various countries in relation to policy efforts to control it. The study was conducted by literature review. The articles studied are limited between 2016 and 2024. It was found that there were 312 articles and there were 8 articles that were suitable for review. The results of this study provide an understanding that the elasticity of cigarette price demand in the world has important implications for cigarette consumption control policies. The policy of increasing cigarette prices will cause high elasticity of cigarette prices, increasing cigarette prices can be an effective strategy to reduce cigarette consumption.